The Civil Law Review Of The Role Of Joint Village-Owned Business Entities (BUM Desa Bersama) As the Subject of Civil Law (Faculty of Law, Universitas Negeri Semarang, 2018)
Village development in Indonesia demands a growing system of regulations both in the field of village development and its economy so that since the enactment of Law Number 6 of 2014 concerning Villages, Village-Owned Enterprises (BUM Desa) have emerged to support economic development and development of a village in Indonesia . BUM Desa is a Legal Entity that can carry out legal actions to manage capital and assets owned, provide general public services in the form of drinking water management, village waste management, management of barns, making ponds, managing plantation products and livestock products, utilizing tourism potential into villages tourism and other business activities that involve the active role of independent village communities, establish partnerships and cooperation with other parties, both individuals and other legal entities such as Limited Liability Companies, CVs and so on. The purpose of this study is to find out the role of the role of the Joint Village Business Entity as the subject of Civil Law in carrying out various legal actions including cooperating in various fields with other business entities incorporated.Keywords: Civil Law, Joint Village Owned Enterprises (BUM Desa Bersama), Subjects of Civil Law